Are You In or Are You Out? The Importance of Group Saliency in Own-Group Biases in Face Recognition. (June 2020) - Harrison, V.; Hole, G.; Habibi, Ruth
Previous research has demonstrated several own-group biases (OGBs) in face recognition, but why they occur is unclear. Social–cognitive accounts suggest they stem from differential attention and facial processing, following the categorisation of a face as belonging to an "in" or "out" group. Three studies explored whether OGBs can be produced by mere categorisation at encoding and investigated the role of in-group membership saliency on face recognition. Participants saw 40 facial images fictionally grouped according to in-/out-group status. Studies 1 and 2 used university membership as the grouping variable and found no evidence of an OGB, and no relationship between OGB magnitude and salience of group membership. Study 3 used the same design as Study 2, but with a highly salient group characteristic: participants' stance on the U.K. Referendum (i.e., whether they were "Leave" or "Remain" supporters). In this case, an asymmetrical OGB was found, with only Remain voters demonstrating an OGB. Furthermore, a relationship between OGB magnitude and attitude toward the Referendum result was found. Overall, our results suggest that social categorisation and membership saliency alone may not be enough to moderate in- and out-group face recognition. However, when sufficiently polarised groups are used as in-/out-group categories, OGBs may occur.